Does Health Literacy Make a Difference? Comparing the Effect of Conventional Medicine Versus Homeopathic Prescribing on Treatment Credibility and Expectancy - Wilhelm, Marcel; Euteneuer, Frank (Frontiers in Psychology, 2021)
Objective: While homeopathic remedies are often used to treat non-specific complaints such as headaches, empirical evidence suggests their treatment effect is due to placebo. Low health literacy seems to be connected to higher use of complementary and alternative medicine (CAM). The aim of this study was to examine what people with occasional headaches expect from conventional medicine or homeopathic remedies and if health literacy interacts with this expectation. Methods: In this experimental study, n = 582 participants with occasional headaches were randomized to read one of two vignettes, which described the prescription of either conventional medicine or a homeopathic remedy. Subsequently, the participants were asked to rate treatment credibility and expectancy with regard to their assigned vignette. Health literacy was assessed as a potential moderator. Results: Participants in the conventional medicine group rated treatment credibility and expectancy higher than in the homeopathic remedy group. Moderation analysis revealed that when being offered conventional medicine, participant reports of treatment credibility and expectancy decreased with lower health literacy, while these outcomes increased with lower health literacy for homeopathic remedies. Discussion: People with occasional headaches estimate the effectiveness of conventional medication properly. However, health care professionals should pay special attention to patients with low health literacy, as they might need more time and information to give their informed consent.